Absolute Baltic Sea Level Trends in the Satellite Altimetry Era: A Revisit - Passaro, Marcello; Müller, Felix L.; Oelsmann, Julius; Rautiainen, Laura; Dettmering, Denise; Hart-Davis, Michael G.; Abulaitijiang, Adili; Andersen, Ole B.; Høyer, Jacob L.; Madsen, Kristine S.; Ringgaard, Ida Margrethe; Särkkä, Jani; et al. (Frontiers in Marine Science, 2021)
The absolute sea level trend from May 1995 to May 2018 in the Baltic Sea is analysed by means of a regional monthly gridded dataset based on a dedicated processing of satellite altimetry data. In addition, we evaluate the role of the North Atlantic Oscillation and the wind patterns in shaping differences in sea level trend and variability at a sub-basin scale. To compile the altimetry dataset, we use information collected in coastal areas and from leads within sea-ice. The dataset is validated by comparison with tide gauges and the available global gridded altimetry products. The agreement between trends computed from satellite altimetry and tide gauges improves by 9%. The rise in sea level is statistically significant in all the region of study and higher in winter than in summer. A gradient of over 3 mm/yr in sea level rise is observed, with the north and east of the basin rising more than the south-west. Part of this gradient (about 1 mm/yr) is directly explained by a regression analysis of the wind contribution on the sea level time series. A sub-basin analysis comparing the northernmost part (Bay of Bothnia) with the south-west reveals that the differences in winter sea level anomalies are related to different phases of the North-Atlantic Oscillation (0.71 correlation coefficient). Sea level anomalies are higher in the Bay of Bothnia when winter wind forcing pushes waters through Ekman transport from the south-west towards east and north. The study also demonstrates the maturity of enhanced satellite altimetry products to support local sea level studies in areas characterised by complex coastlines or sea-ice coverage. The processing chain used in this study can be exported to other regions, in particular to test the applicability in regions affected by larger ocean tides.